Large Genomic Rearrangements in the Hepatocyte Nuclear Factor-1β (TCF2) Gene Are the Most Frequent Cause of Maturity-Onset Diabetes of the Young Type 5 - Bellanné-Chantelot, Christine; Clauin, Séverine; Chauveau, Dominique; Collin, Philippe; Daumont, Michèle; Douillard, Claire; Dubois-Laforgue, Danièle; Dusselier, Laurent; Gautier, Jean-François; Jadoul, Michel; Laloi-Michelin, Marie; Jacquesson, Laetitia; et al. (Diabetes (New York, N.Y.), 2005)
Large Genomic Rearrangements in the Hepatocyte Nuclear Factor-1β ( TCF2 ) Gene Are the Most Frequent Cause of Maturity-Onset Diabetes of the Young Type 5 Christine Bellanné-Chantelot 1 , Séverine Clauin 1 , Dominique Chauveau 2 , Philippe Collin 3 , Michèle Daumont 4 , Claire Douillard 5 , Danièle Dubois-Laforgue 6 , Laurent Dusselier 7 , Jean-François Gautier 8 , Michel Jadoul 9 , Marie Laloi-Michelin 10 , Laetitia Jacquesson 11 , Etienne Larger 12 , Jacques Louis 7 , Marc Nicolino 13 , Jean-François Subra 14 , Jean-Marie Wilhem 15 , Jacques Young 16 , Gilberto Velho 17 and José Timsit 6 1 Department of Cytogenetics and Molecular Biology, Hôpital Saint-Antoine, Assistance Publique-Hôpitaux de Paris, Paris, France 2 Department of Nephrology, Hôpital de Rangueil, Toulouse, France 3 Department of Internal Medicine, Centre Hospitalier de Niort, Niort, France 4 Department of Endocrinology, Centre Hospitalier de Vienne, Vienne, France 5 Department of Endocrinology, Centre Hospitalier de Béthune, Béthune, France 6 Department of Immunology and Diabetology, Paris Descartes University, Hôpital Cochin, Assistance Publique-Hôpitaux de Paris, Paris, France 7 Department of Endocrinology, Hôpital Sainte-Blandine, Metz, France 8 Department of Endocrinology, Hôpital Saint-Louis, Assistance Publique-Hôpitaux de Paris, Paris, France 9 Cliniques Saint-Luc, Université Catholique de Louvain, Bruxelles, Belgium 10 Department of Internal Medicine, Hôpital Lariboisière, Assistance Publique-Hôpitaux de Paris, Paris, France 11 Department of Endocrinology, Hôpital Saint-Antoine, Assistance Publique-Hôpitaux de Paris, Paris, France 12 Department of Endocrinology, Hôpital Bichat, Assistance Publique-Hôpitaux de Paris, Paris, France 13 Department of Endocrinology, Hôpital Debrousse, Lyon, France 14 Department of Nephrology, Centre Hospitalier Universitaire d’Angers, Angers, France 15 Department of Internal Medicine, Centre Hospitalier Saint-Morand, Altkirch, France 16 Department of Endocrinology, Hôpital de Kremlin-Bicêtre, Assistance Publique-Hôpitaux de Paris, Le Kremlin-Bicêtre, France 17 Inserm U695, Faculté de Médecine Xavier Bichat, Paris, France Address correspondence and reprint requests to Christine Bellanne-Chantelot, Hopital Saint Antoine, Service de Cytogenetique, 184 Rue du Faubourg Saint-Antoine, 75012 Paris, France. E-mail: christine.bellanneatsat.ap-hop-paris.fr Abstract Maturity-onset diabetes of the young (MODY) 5 is caused by mutations in the TCF2 gene encoding the transcription factor hepatocyte nuclear factor-1β. However, in 60% of the patients with a phenotype suggesting MODY5, no point mutation is detected in TCF2 . We have hypothesized that large genomic rearrangements of TCF2 that are missed by conventional screening methods may account for this observation. In 40 unrelated patients presenting with MODY5 phenotype, TCF2 was screened for mutations by sequencing. Patients without mutations were then screened for TCF2 rearrangements by the quantitative multiplex PCR of short fluorescent fragments (QMPSF). Among the 40 patients, the overall detection rate was 70%: 18 had point mutations, 9 had whole-gene deletions, and 1 had a deletion of a single exon. Similar phenotypes were observed in patients with mutations and in subjects with large deletions. These results suggest that MODY5 is more prevalent than previously reported, with one-third of the cases resulting from large deletions of TCF2 . Because QMPSF is more rapid and cost effective than sequencing, we propose that patients whose phenotype is consistent with MODY5 should be screened first with the QMPSF assay. In addition, other MODY genes should be screened for large genomic rearrangements. HNF, hepatocyte nuclear factor MODY, maturity-onset diabetes of the young QMPSF, quantitative multiplex PCR of short fluorescent fragments STS, sequence-tagged site Footnotes Additional information for this article can be found in an online appendix at http://diabetes.diabetesjournals.org . Accepted July 25, 2005. Received April 27, 2005. DIABETES